Sodium Hypochlorite in Endodontic Therapy: Immutable Hero or Imminent Threat? - García-Torres, Edgar (Odovtos - International Journal of Dental Sciences, 2024)
Historically, in its beginnings, sodium hypochlorite was only related to the bleaching of garments, however, over the years its use was extended to the medical area thanks to its disinfectant qualities, and its application continued in the field of dentistry, especially in endodontics, so much so that it has come to be considered today the gold standard in endodontic irrigation. This article aims to briefly highlight its importance in endodontics and the qualities that allow its continued use.